MEDIA TORSO DALAM MEMANTAPKAN VISUALISASI KOSAKATA BAHASA ARAB SISWA DI MADRASAH - Fathor Rozi; Abd. Hamid Wahid; Siti Azimul Faiqe (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
The aim of this research was to reveal the process of using torso media in strengthening the visualization of students' Arabic vocabulary. The research method used a qualitative approach with a field research type. Data was collected from a non-participant observation process, in-depth interviews with the Head of Madrasah, Deputy Head of Curriculum, and Arabic language teachers. Then the data obtained was analyzed using techniques from Miles, Huberman, and Saldana, namely data condensation, data presentation, and drawing conclusions. Finally, data validity was carried out through source and technical triangulation techniques. The success of this research was certainly able to make students easily memorize and remember Arabic vocabulary for each part of the body. This research improved students' fine (visual) motor skills which is supported by the use of torso media. The results of this research also ensured students' understanding by providing motivation to be confident in conveying their learning results, and not to be afraid of making mistakes, by explaining that making mistakes in answering is normal in learning. This condition must be maintained in learning activities so that the expected goals can be achieved.